FATHER'S ROLE IN CHILD EDUCATION PERSPECTIVE OF AL-QUR'AN SURAH LUQMAN VERSES 12-19 (TAFSIR AL-QURTHUBI, TAFSIR IBNU KATSIR, TAFSIR FI ZHILALIL QUR'AN AND TAFSIR AL-MUNIR) - Winarti, Anastasia; Ashari, Suhartini (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2024)
This study provides a more detailed picture of the role of fathers in educating children from the perspective of the Qur'an, Surah Luqman (31), verses 12–19. So far, there has been a perception in Indonesian society that the problem of children's education is the sole responsibility of a mother because the father has the responsibility to fulfill economic needs. The social phenomena that occur in several regions in Indonesia related to the gap in children's behavior are examined through the interpretation of al-Qurthubi, the interpretation of Ibn Kathir, the understanding of Fi Zhilalil Qur'an, and the interpretation of al-Munir. Method: This study used qualitative research. Qualitative research is used to investigate, find, describe, and explain the quality or characteristics of social influences that cannot be explained, measured, or described. This research takes a study of tafsir literacy from four mufasir, namely tafsir al-Qurthubi, tafsir Ibnu Katsir, tafsir Fi Zhilalil Qur'an and tafsir al-Munir Finding: The importance of the father's role in children's education, told with advice to (1) Be grateful to Allah Subhânahu wa ta'âlâ, (2) Avoid all forms of shirk, (3) Be devoted to both parents, and (4) Always maintain awareness of muraqabah or Allah Subhânahu wa ta'âlâ's supervision over all things, both small and large. (5) The command to uphold prayer, enjoin makruf, nahi munkar. (6) The command not to be arrogant and haughty; (7) walk politely and lower your tone of voice. Novelty: This study is the only one that explains the role of fathers in children's education from the perspective of the Qur'an, Surah Luqman (31) verses 12 to 19, with an analysis of the interpretation of al-qurthubi, interpretation of Ibn Kathir, interpretation of fi zhilalil Qur'an and interpretation of al-munir. The results of the study show that based on the Qur'an, the role of fathers in children's education is very important and strategic for building the future civilization of the people.